2014
DOI: 10.1073/pnas.1318951111
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p53 preserves Parkin-mediated mitophagy and pancreatic β-cell function in diabetes

Abstract: Mitochondrial compromise is a fundamental contributor to pancreatic β-cell failure in diabetes. Previous studies have demonstrated a broader role for tumor suppressor p53 that extends to the modulation of mitochondrial homeostasis. However, the role of islet p53 in glucose homeostasis has not yet been evaluated. Here we show that p53 deficiency protects against the development of diabetes in streptozotocin (STZ)-induced type 1 and db/db mouse models of type 2 diabetes. Glucolipotoxicity stimulates NADPH oxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(160 citation statements)
references
References 32 publications
10
149
1
Order By: Relevance
“…Consistently, p53 knockdown prevented the decrease in mitochondrial membrane potential and inhibited mitochondrial ROS accumulation. Our results are in line with previous studies that show that the p53‐parkin inhibition pathway plays an important role in cardiac ageing and drives age‐related diseases, such as heart failure and diabetes (Hoshino et al, 2014, 2013 ). Notably, we provide additional mechanistic evidence that p53 is a major mediator of the MAO‐A‐dependent response.…”
Section: Discussionsupporting
confidence: 93%
“…Consistently, p53 knockdown prevented the decrease in mitochondrial membrane potential and inhibited mitochondrial ROS accumulation. Our results are in line with previous studies that show that the p53‐parkin inhibition pathway plays an important role in cardiac ageing and drives age‐related diseases, such as heart failure and diabetes (Hoshino et al, 2014, 2013 ). Notably, we provide additional mechanistic evidence that p53 is a major mediator of the MAO‐A‐dependent response.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a study reported that Parkin-mediated mitophagy is protective in pancreatic ␤-cell function in diabetes (30). Diabetic cardiomyopathy is associated with mitochondrial dysfunction (6), and it is possible that impaired autophagy and mitophagy may contribute to the pathology.…”
Section: H188mentioning
confidence: 99%
“…At the onset of diabetes, the tumor suppressor protein p53 accumulates in the cytosol of mouse b-cells and inhibits PARKIN-mediated mitophagy. Mice deficient in p53 have restored mitophagy and are resistant to b-cell loss induced by streptozotocin (STZ) (63). The PINK1/PARKIN pathway plays an important role in mitochondrial quality control in the heart (16,68,90).…”
Section: Mitochondrial Autophagymentioning
confidence: 99%
“…As a result, the removal of damaged mitochondria is abrogated and dysfunctional mitochondria accumulate, leading to cardiac functional decline (64). Inhibition of PARKIN-mediated mitophagy by p53 has also been linked to impaired function of pancreatic b-cells in T1D (63). However, whether cytosolic p53 contributes to the development of diabetic cardiomypathy by inhibiting PARKIN-mediated mitophagy in myocytes remains to be determined.…”
Section: Mitophagy and P53 In Diabetesmentioning
confidence: 99%